2018
DOI: 10.1530/eje-17-0986
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular features of possible autonomous cortisol secretion in patients with adrenal incidentalomas

Abstract: In apparently asymptomatic patients, mild autonomous cortisol secretion can sustain early cardiac and vascular remodeling, independently of other risk factors. The morphological and functional cardiovascular changes observed in pACS underline the need for further studies to correctly define the long-term management of this relatively common condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 34 publications
2
45
0
1
Order By: Relevance
“…The present data provide strong evidence to support the view that patients with adrenal incidentalomas have a worse metabolic profile, which is associated with increased cardiovascular risk (13)(14)(15)(16)18). The observation that diabetes was an independent predictor of the presence of adrenal tumors points to the relationship with insulin resistance, which may be bidirectional, as recently argued by Sydney et al (30).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The present data provide strong evidence to support the view that patients with adrenal incidentalomas have a worse metabolic profile, which is associated with increased cardiovascular risk (13)(14)(15)(16)18). The observation that diabetes was an independent predictor of the presence of adrenal tumors points to the relationship with insulin resistance, which may be bidirectional, as recently argued by Sydney et al (30).…”
Section: Discussionsupporting
confidence: 86%
“…Autonomous cortisol secretion has been defined as subclinical Cushing's syndrome or subclinical hypercortisolism, and represents the lower end of the Cushing's syndrome spectrum. An increasing body of evidence suggests that is associated with metabolic and cardiovascular diseases that may eventually result in excess mortality (13)(14)(15)(16)(17)(18)(19).…”
Section: Most Adrenal Incidentalomas Are Benign Cortical Adenomas Thamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, eGFR measured by serum creatinine can be overestimated in patients with hypercortisolism. In a recent study showing association between hypercortisolism and cardiac function [23], serum creatinine levels were not significantly different among NFA with pACS, however, this report did not compare eGFR estimated by multiple parameters including serum creatinine and cystatin. The present study is the first to address this important issue, and found that eGFRcre is overestimated even in the pACS patients without Cushing syndrome.…”
Section: Discussionmentioning
confidence: 61%
“…Recent evidence highlighted that cardiac performance may be al tered in patients with hypercortisolism, adding interesting and novel features to the cardiovascular profile of patients with ACS. A recent crosssectional analysis of a large cohort of patients with in cidentalomas revealed that left ventricular mass index, a marker of cardiac hypertrophy associated with hypertension, and pulse wave velocity, a marker of arterial stiffness, were significantly higher in patients with ACS [17]. Moreover, concentric and eccentric left ven tricular hypertrophy was more prevalent in patients with ACS.…”
Section: Risk Of Cardiovascular Diseasesmentioning
confidence: 99%